Risk Assessment of Trade Barriers: The Implications of Indonesia's Halal Certification Law on International Commerce - Amijaya, Rachmania Nurul Fitri; Asa Prayarsni Korina; Rochmatulloh Alaika; Hilda Lutfiani (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2024)
Introduction: The importance of halal standards in international commerce has increased as the volume of cross-border trade has increased. This article investigates the ramifications of Indonesia's Halal Product Guarantee Law on global trade, specifically focusing on its arrangement with World Trade Organization rules, explicitly the Specialized Technical Barriers to Trade Agreement. Even though the Halal Product Guarantee Law requires halal certification, it could be seen as a trade barrier because it could impose too many regulations and encourage discrimination against imported goods. Objective: This study discusses the implications for international trade of the Halal Product Guarantee Law's potential violations of the Technical Barriers to Trade Agreement and emphasizes the necessity of globally consistent and uniform halal certification standards. Method: This study analyzes the Halal Product Guarantee Law about important World Trade Organization principles like National Treatment and Most Favored Nation using a descriptive qualitative research methodology and drawing from previous literature reviews. Result: According to the findings, the Halal Product Guarantee Law may violate World Trade Organization regulations, which would have a significant impact on international trade and raise questions regarding the uniformity, adaptability, and consistency of halal certification. Implication: The article emphasizes the significance of evaluating the Halal Product Guarantee Law's compliance with World Trade Organization agreements to support the expansion of the halal market, respect religious beliefs, and ensure fair and balanced international commerce.